Congenital Tuberculosis in a Neonate: A Case Report and Literature Review - Yeh, Jui-Ju; Lin, Sheng-Chieh; Lin, Wen-Chuan (Frontiers in Pediatrics, 2019)
Congenital tuberculosis (TB) is difficult to detect because the disease presents few or no symptoms in the fetus during pregnancy and nonspecific symptoms in neonates. We reviewed 20 cases of congenital TB reported between 2011 and 2017 and report a case of a mother and her 8-day-old neonate with congenital TB. In these 21 cases (including our case), the most common clinical presentations were respiratory distress, fever, and hepatosplenomegaly. The most common chest imaging findings were pneumonia, multiple pulmonary nodules, and miliary pattern. The mortality rate of infants with TB was increased approximately 2.2-fold if their mothers had no symptoms. The case reported herein concerns an 8-day-old neonate with the rare presentation of a 2-day history of fever, followed by abdominal distension without respiratory symptoms. Computed tomography (CT) imaging exhibited a large amount of right pleural effusion. Multiple antimicrobial therapies were administered to the neonate; however, his symptoms persisted. Repeat CT was used to identify a progressed disease with multiple nodules over the lung, spleen, and hepatic hilar region. Standard anti-TB medications were prescribed, and the patient recovered gradually. Both gastric lavage and pleural effusion cultures confirmed the diagnosis of TB. The neonate’s mother denied any TB contact history and the diagnosis of any medical disease during pregnancy, but she experienced a fulminant course of miliary TB and was admitted to the intensive care unit 24 days postpartum. She died despite receiving anti-TB treatment. In TB-endemic areas, congenital TB should be taken into consideration when neonates develop fever, respond poorly to antimicrobial treatment, and when their mothers deny any TB contact history.